Leveraging Artificial Intelligence and Text Analysis for Enhanced Understanding of Complex Social Phenomena: A Computational Approach to Social Science Research - Pedrawi, Alan (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The intersection of artificial intelligence and social science research has opened unprecedented opportunities for understanding complex social phenomena through advanced text analysis methodologies. This paper examines the application of computational linguistics, natural language processing, and machine learning techniques in analyzing large-scale textual data to extract meaningful insights about societal patterns, behaviors, and trends. Through a comprehensive review of current methodologies and empirical analysis of diverse textual datasets including social media content, news articles, and public discourse, this study demonstrates the transformative potential of AI-driven text analysis in social research. The research employs a mixed-methods approach, combining quantitative computational analysis with qualitative interpretation frameworks to evaluate the effectiveness of various AI models in identifying, categorizing, and predicting social phenomena. Results indicate that advanced neural networks, particularly transformer-based architectures, demonstrate superior performance in capturing nuanced social dynamics compared to traditional statistical methods. However, the study also reveals significant challenges related to bias mitigation, cultural context preservation, and ethical considerations in automated social analysis. The findings suggest that while AI-powered text analysis offers remarkable capabilities for large-scale social research, successful implementation requires careful attention to methodological rigor, interdisciplinary collaboration, and ethical frameworks. This research contributes to the growing body of literature on computational social science by providing empirical evidence for the efficacy of AI approaches while highlighting critical considerations for future research directions.